Penerapan Teknik Relaksasi Otot Progresif Terhadap Tekanan Darah Pasien Hipertensi - Ami Dwi Nurul Salmi (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2023)
Hypertension is defined as a systolic pressure of more than 160 mmHg and a diastolic pressure of more than 90 mmHg. Progressive Muscle Relaxation Technique can be an exercise choice in restraining the stress response and relieving muscle tension consciously. The aim of this research is to determine the effect of progressive muscle relaxation techniques on blood pressure in the Andalas Padang Health Center working area in 2023. This type of research is pre-experimental with a One Group Pretest-Posttest design approach. The research was carried out from August – November 2023. Univariate and bivariate analysis of the results used the paired T-test statistical test. The sample in this study was 12 people using purposive sampling technique. The average blood pressure before applying the progressive muscle relaxation technique was systolic mean 157.33 mmHg and diastolic mean 93.67 mmHg. The average blood pressure after applying the progressive muscle relaxation technique was a mean systolic of 132.30 mmHg and a mean diastolic of 86.67 mmHg. There is an effect of providing progressive muscle relaxation techniques on blood pressure. It is hoped that this research can provide a contribution based on scientific evidence to serve as reference material for education and distribution of leaflets so that hypertension sufferers in the target area can implement structured progressive muscle relaxation therapy exercises as an appropriate non-pharmacological treatment effort. Keywords: Blood Pressure; Hypertension; Progresif Muscle Relaxation